Monster Bugs - Penner, Lucille Recht; Nang Chan Yeema (New York. USA Random House, 2003)
Describes some of the world's largest insects and spiders, including the Goliath beetle, praying mantis, tarantula, and giant atlas moth.
Keywords: Level Books